(untitled) (Scientific journal of the Fergana State University, 2024)
The Shohimardonsoy-Margilonsoy river is considered one of the ancient rivers in the Fergana valley. The total length of the river is 112 km. During observations, it was found that there are 17 species belonging to 11 families and 5 orders in this river. 6 of them are endemic species. Moreover, 2 species (Cottus spinulosus, Glyptosternon oschanini) are included in the Red Data Book of the Republic of Uzbekistan